Car MAX-DOAS measurements around entire cities: quantification of NOx emissions from the cities of Mannheim and Ludwigshafen (Germany) - Ibrahim, Ossama; Shaiganfar, R.; Sinreich, Roman; Stein, T.; Platt, Ulrich; Wagner, T. (Atmospheric measurement techniques, 2010)
We present car Multi-Axis (MAX-) DOAS observations of tropospheric NO2 carried out on circles around the cities of Mannheim and Ludwigshafen (Germany) on 24 August 2006. Together with information on wind speed and direction, the total emissions of the encircled source(s) are quantified from these measurements. In contrast to recent similar studies based on zenith scattered sun light (elevation angle of 90°), we use a MAX-DOAS instrument mounted on a car, which observes scattered sun light under different elevation angles (here 45°, and 90°). Compared to simple zenith sky observations, MAX-DOAS observations have higher sensitivity and reduced uncertainty, and avoid systematic offsets in the determination of the vertically integrated trace gas concentration. The determination of the absolute value of the integrated tropospheric trace gas concentrations is especially important for the calculation of absolute trace gas fluxes through arbitrary transects. However, even if emission sources are completely surrounded, systematic offsets in the measured vertically integrated trace gas concentration can lead to errors in the determined total emissions, especially for observations around extended areas. In this study we discuss and quantify different error sources. In most cases, the largest error source is the variability and imperfect knowledge of the wind field. In addition - depending on the trace species observed - also chemical transformations between the emission sources and the measurement location have to be considered. For that purpose we use local observations within the encircled area to quantify and/or correct these errors. From our observations we derive a total NOx emission from the Mannheim/Ludwigshafen area of (7.4±1.8)×1024 molec/sec, which if assumed to be constant throughout the year would correspond to a total emission of 17 830±4340 t/yr (calculated with the mass of NO2 t/yr, consistent with existing emission estimates. From our observations it is also possible to separately determine the average influx into the Mannheim/Ludwigshafen area (5.4±0.9×1024 molec/sec or 13 010±2170 t/yr) and the average outflux (12.8±1.8×1024 molec/sec or 13 010±4340 t/yr).